Fundamentals of management : text and Philippine cases - Rodriguez, Rafael A.; Echanis, Erlinda S. ([Manila, Philippines] : Diwata Publishing, Inc, 2001)
The current edition incorporates a number of additions to update the text with current material. Foremost among these is a discussion on the Internet and e-commerce.
Part 1 - Introduction -- Part 2 The Management process -- Part 3 Business Management Functions.
Includes index.
Keywords: MANAGEMENT -- PHILIPPINES